2013
DOI: 10.4103/0976-9668.107263
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorating effect of mother tincture of Syzygium jambolanum on carbohydrate and lipid metabolic disorders in streptozotocin-induced diabetic rat: Homeopathic remedy

Abstract: Background:Syzygium jambolanum (S jambolanum) is widely used in homeopathy for treating patients with diabetes mellitus. In the present study, an attempt has been made to investigate the remedial effect of homeopathic drug S jambolanum on carbohydrate and lipid metabolic disorders on streptozotocin induced diabetic rat.Materials and Methods:Diabetes induction in Wistar strain rat was performed as per standard method using streptozotocin at the dose of 4 mg/100 gm body weight. Activities of carbohydrate metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…ALT and AST transaminases are closely linked biomarkers to hepatic tissue damage [60]. It has been established that the increase of serum activities of transaminases, GGT, and ALP in T2D-induced rats may be due to hepatic injury linked with STZ resulting in leakage of these enzymes from the liver into plasma [61]. The current study has shown that treatment with Se-NPs and/or MET as monotherapy and also combined therapy restored the activities of ALT, AST, GGT and ALP toward normal levels as well as the levels of albumin, total protein and bilirubin returned near to normal levels.…”
Section: Discussionmentioning
confidence: 99%
“…ALT and AST transaminases are closely linked biomarkers to hepatic tissue damage [60]. It has been established that the increase of serum activities of transaminases, GGT, and ALP in T2D-induced rats may be due to hepatic injury linked with STZ resulting in leakage of these enzymes from the liver into plasma [61]. The current study has shown that treatment with Se-NPs and/or MET as monotherapy and also combined therapy restored the activities of ALT, AST, GGT and ALP toward normal levels as well as the levels of albumin, total protein and bilirubin returned near to normal levels.…”
Section: Discussionmentioning
confidence: 99%
“…Transaminases (ALT and AST) are extremely sensitive biomarkers that have been directly associated with toxicity and liver impairment [56]. According to Ghosh et al, signifcant elevations in ALT and AST activity in the serum of diabetic rats may be primarily caused by the leakage of these enzymes from the liver cytosol into the circulation as a result of hepatic damage linked to STZ [57]. Te results of the HFD/STZ group in the present study were matched with the previous studies [56,58,59].…”
Section: Discussionmentioning
confidence: 99%